Motivasi Kerja dalam Organisasi Pendidikan - Anisa Wahyuni; Elva Siti Fatimah; Bambang Samsul Arifin (STAI Terpadu Yogyakarta, 2021)
In fact, a person's attitude is determined by his desire to achieve a goal. Another term of will is motivation. Motivation is the motivation for a person to carry out activities to achieve his goals. The power of motivation for a person can change at any time. The change occurs because of satisfaction with the needs. Such satisfied needs have motivated one's attitude. Motivation is needed because with this motivation it is expected that everyone can work hard and be eager to achieve high work productivity. Instilling motivation is basically instilling values. Therefore, communication and continuous coaching are key, with the motivation of work in performing tasks can optimize the achievement of processes that run easily, orderly, and conducive in achieving goals. With increased motivation, it can help employees behave and behave with responsibility. These motivations need to be developed to improve work achievement and job satisfaction which will ultimately increase the productivity of organizations in the field of education, namely the quality of schools as educational institutions.